SOSIALISASI PENGKONSUMSIAN MINUMAN BERENERGI PADA FUNGSI GINJAL DI DESA TARUB - Estuningtyas Ayu Hapsari; Supriyanto; Fani Nurjumiati; Rara Erika (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: The increase in unhealthy lifestyles, including excessive consumption of energy drinks among people, especially those of productive age, can have a negative impact on kidney function. This type of drink contains caffeine, sugar and other stimulants which, if consumed long term, can cause health problems, including kidney damage. Purpose: This Community Service Activity (PkM) aims to increase the understanding of the Tarub Village community about the dangers of consuming energy drinks and the negative impact on kidney function and body health. Method: The methods used are interactive lectures, group discussions, evaluative quizzes and educational posters equipped with attractive images and infographics. Results: The results of the activity showed that 85% of residents understood the material well regarding the dangers of consuming energy drinks, and around 60% of residents began to reduce their consumption of energy drinks and choose alternative healthy drinks. Conclusion: This activity proves that educational outreach can be an effective means of increasing public health awareness.